P138 Psychometric validation and interpretation of a patient-reported outcomes instrument to assess bowel urgency among adults with moderate to severe Ulcerative Colitis. (21st January 2022) - Dubinsky, M C; Delbecque, L; Lewis, J; Hunter, T; Shan, M
Abstract: Background: Urgency, the sudden or immediate need for a bowel movement, is one of the most bothersome symptoms experienced by Ulcerative Colitis (UC) patients. We aimed to evaluate the psychometric properties of the Urgency Numeric Rating Scale (UNRS), inform the clinically meaningful within-patient change (MWPC) threshold and determine the UNRS threshold associated with clinical, endoscopic and histologic remission. Methods: In this study, the UNRS was collected daily through an electronic diary that measures the severity of the urgency to have a bowel movement in the past 24 hours using an 11-point NRS ranging from 0 (no urgency) to 10 (worst possible urgency). A weekly score was calculated for a 7-day period by averaging the observed entries if 4 or more observations are available. Item performance, reliability, validity, responsiveness, and score interpretation were assessed at baseline (BL) and week 12 in moderate-severe patients with UC enrolled in a multicenter, randomized, placebo-controlled Phase 3 study. Results: The full distribution of responses was provided by patients at BL and Week 12, with no floor or ceiling effects. Test-retest reliability was strong, with intra-class correlation coefficients ranging 0.76–0.89. As expected, moderate to high correlations were seen between the UNRS and health-related quality of life measures, patient ratings of UC severity, disease change, stool frequency and rectal bleeding (establishing convergent validity), while low correlations were seen with endoscopy and histology measures (establishing discriminant validity) (Table 1). As predicted, statistically higher UNRS scores were found in patients with more severe UC compared to those with less severe UC, providing evidence of known groups validity. Findings also indicated the UNRS is responsive to changes over time. Anchor-based analyses suggested that a 3-point score reduction from BL to week 12 constitutes a MWPC (Figure 1). A UNRS score of 0, 1, or 2 best reflected urgency severity level when patients were in clinical (YI=0.36), histologic (YI=0.27), or endoscopic remission (YI=0.27) (Table 2). A UNRS score of 0 or 1 may be a more conservative endpoint to define patients with no to minimal urgency. Conclusion: The UNRS is a valid and reliable patient-reported measure of urgency in adults with UC. A 3-point improvement is a MWPC threshold. A UNRS score of 0 or 1 is a conservative threshold that reflects clinical, endoscopic and histologic remission. These findings provide strong evidence supporting that the UNRS is appropriate for inclusion as an endpoint in clinical trials to evaluate UC treatments efficacy.